(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Studies have shown that indoor thermal comfort is crucial for human well-being, particularly in the built environment, and those factors such as solar gain, building design, and occupancy status can significantly impact thermal comfort. This study aims to model and estimate thermal comfort and annual energy loads for a typical residential building in Bauchi, Nigeria. A three-bedroom residential building was modelled using SketchUp and TRNSYS, supported by MATLAB, to simulate HVAC, hot water, and electrical energy demands based on local climatic and usage data. Results show that indoor temperatures exceeding the thermal comfort threshold of 27°C by approximately 92% of the year, with peak cooling demand in March and April. Hot water consumption accounted for the highest energy load, contributing significantly to an annual total of approximately 11,746.6 kWh. These results have significant implications for energy-efficient building design, HVAC system sizing, and renewable energy integration. Additionally, solar energy can help meet peak cooling demands during dry season months. Understanding these factors and incorporating energy-efficient design principles, buildings can be designed to provide optimal thermal conditions while minimizing energy consumption. These insights underscore the need for energy-efficient building strategies and support the adoption of Photovoltaic-Thermal systems to enhance energy sustainability in hot climate regions.